PENGARUH METODE SUKU KATA (SYLLABIC METHOD) BERBANTUAN MEDIA DIGITAL GENIALLY TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SEKOLAH DASAR - Apriliyani, Annisa; Nurmahanani, Indah; Wahyudin, D. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Reading is one that is needed in the learner to smooth dama teaching and learning activities. However, attention in developing students ' initial reading skills is still limited. there are students who are still lacking in recognizing letters and reading fluently. it is necessary to develop appropriate learning methods, one of which is the syllabic method assisted by Genilly digital media. The researchers used a Pre-Experimental Design approach . The population in this study using purposive sampling technique to obtain students Grade 1 Sdn Cemara Kulon totaling 32 students. The instruments used in the study are teacher and student observation sheets, teaching modules, reading ability instruments. In early reading, there is a benchmark for achieving the goal of early reading in the first grade, namely the EGRA test .To collect data on the ability to read the beginning used observations that meteruji validity and reliability. So it can test the hypothesis with T test, linear regression test, and N-Gain test to see how much the increase. The results showed that there is an effect of syllabic method (syllabic method) assisted by Digital Media Genially influence given by 80.7% with an average increase of 0.32 with the medium category. From the results of the data description, it can be concluded that there is an effect of the syllabic method (syllabic method) assisted by digital media genially on the ability to read the beginning of Grade 1 elementary school students.